Building Tolerance Among Elementary School Students in Multicultural Education from Elementary School to College - Rajaloa, Nani I.; Hasmawati, Hasmawati; Djumat, Irwan (Mimbar Sekolah Dasar, 2025)
The level of tolerance and appreciation for cultural diversity among elementary and university students remains relatively low. This research is considered urgent because of the discrepancy between societal expectations and the realities observed in educational settings, where tolerance as a foundation for fostering inclusive and harmonious attitudes is still minimal. The purpose of this study is to examine the effectiveness of multicultural education programs in instilling the values of tolerance and respect for cultural diversity. This study employed a quantitative approach with a purposive sample of 370 students. Data were collected through a validated questionnaire and analysed using descriptive statistics, ANOVA, and regression techniques with the assistance of SPSS Version 29.0. The results demonstrate that multicultural education programs significantly enhance students’ tolerant attitudes (F = 58.67, p .001), with a contribution of 41%. In addition, social interaction within groups was found to be effective in developing empathy and strengthening cultural understanding among students. These findings highlight that systematic and sustainable multicultural education can play a pivotal role in shaping a generation that values diversity and demonstrates inclusive behaviour. In conclusion, the study emphasizes the importance of integrating multicultural education into the curriculum, not only as a theoretical concept but also as a practical framework for classroom and community engagement. The implications suggest that collaboration between schools, families, and communities is essential to building an inclusive learning environment that nurtures tolerance, empathy, and mutual respect across cultural boundaries.